People-Powered and Non-Violent Social Movements: Forcing Gradualist Democratic Reforms in Authoritarian Societies - Zunes, Stephen (Frontiers in Political Science, 2022)
Not all successful unarmed civil insurrections against dictatorships take place in a dramatic mass uprising with hundreds of thousands occupying central squares in the capital city. There have also been cases of nonviolent struggles against autocratic regimes that failed to topple the dictatorship in a revolutionary wave, but did succeed in forcing a series of legal, constitutional and institutional reforms over a period of several years that eventually evolved into a liberal democratic order. These more gradualist transitions have taken place across different regions and against different kinds of authoritarian systems. This webinar will tell the story of pro-democracy movements in three of these countries—Brazil, South Korea and Kenya—and how they were able to force, over time, autocratic governments to agree to substantive democratic reforms. By focusing on the role of civil society, this presentation challenges dominant, top-down, institution- and elite-based approaches to democratization.